Physician Barriers and Facilitators for Screening for Congenital Heart Disease With Routine Obstetric Ultrasound: A National United States Survey. (24th December 2019) - Pinto, Nelangi M.; Henry, Kevin A.; Grobman, William A.; Ness, Amen; Miller, Stephen; Ellestad, Sarah; Gotteiner, Nina; Tacy, Theresa; Wei, Guo; Minich, L. LuAnn; Kinney, Anita Y.
Abstract : Objectives: Prenatal detection of congenital heart disease with obstetric screening remains at less than 50% in most population studies, far from what is thought to be achievable. We sought to identify barriers/facilitators for screening from the perspective of interpreting physicians and to understand how these barriers/facilitators may be associated with interpretation of screening images. Methods: Our mixed‐methods studies included 4 focus groups in centers across the United States with obstetric, maternal‐fetal medicine, and radiology providers who interpreted obstetric ultrasound studies. Themes around barriers/facilitators for fetal heart screening were coded from transcripts. A national Web‐based survey was then conducted, which quantitatively measured reported barriers/facilitators and measured physicians' ability to interpret fetal heart‐screening images. Multivariable generalized linear random‐effect models assessed the association between barriers/facilitators and the accuracy of image interpretation at the image level. Results: Three main themes were identified in the focus groups: intrinsic barriers (ie, comfort with screening), external barriers (ie, lack of feedback), and organizational barriers (ie, study volumes). Among 190 physician respondents, 104 interpreted ultrasound studies. Perceptions of barriers varied by practice setting, with nontertiary providers having lower self‐efficacy and perceived usefulness of cardiac screening. Facilitators associated with the odds of accurate interpretation of screening images were knowledge (odds ratio, 2.54; P = .002) and the volume of scans per week (odds ratio, 1.01 for every additional scan; P = .04). Conclusions: Some of the main barriers to cardiac screening identified and prioritized by physicians across the United States were knowledge of screening and minimal volumes of scans. Targeting these barriers will aid in improving prenatal detection of congenital heart disease.